Value of osteoprotegerin, RANKL, interleukin-17 in mechanisms of bone metabolism disorders - Cheremisina, V. F. (Journal of Education, Health and Sport, 2017)
The relationship between osteoprotegerin, RANKL and interleukin-17 inthe mechanisms of abnormal remodeling of bone tissue during experimental periodontitis was studied in this work. Increased levels of RANKL and pro-inflammatory IL-17 were found, as well as a decrease in the serum osteoprotegerin content of rat experimental rats. The revealed correlations between the level of interleukin-17, RANKL and osteoprotegerin indicate an important role of the studied cytokines in bone remodeling disorders during periodontitis.